Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591730
|View full text |Cite
|
Sign up to set email alerts
|

A clinic compatible, open source electrophysiology system

Abstract: Open source electrophysiology (ephys) recording systems have several advantages over commercial systems such as customization and affordability enabling more researchers to conduct ephys experiments. Notable open source ephys systems include Open-Ephys, NeuroRighter and more recently Willow, all of which have high channel count (64+), scalability, and advanced software to develop on top of. However, little work has been done to build an open source ephys system that is clinic compatible, particularly in the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…A major challenge to increasing the area for such small pitch grids is scaling connectors and amplification circuits. However, we anticipate that advances in technology will make higher channel count systems cheaper and easier to access (Hermiz et al, 2016;Insanally et al, 2016;Trumpis et al, 2017), thus making higher density probes more attractive to use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major challenge to increasing the area for such small pitch grids is scaling connectors and amplification circuits. However, we anticipate that advances in technology will make higher channel count systems cheaper and easier to access (Hermiz et al, 2016;Insanally et al, 2016;Trumpis et al, 2017), thus making higher density probes more attractive to use.…”
Section: Discussionmentioning
confidence: 99%
“…Additional device details can be found in (Ganji et al, 2017;Uguz et al, 2016). The data acquisition system used is described extensively in (Hermiz et al, 2016) and briefly in Section A.1.…”
Section: Probementioning
confidence: 99%
“…Another method for depositing PEDOT:PSS from solution is the spin-coating technique that offers monolithic integration and scalability benefits over electrodeposited PEDOT and has been recently used in high-density neural probe electrophysiology. [1b,11a,18] We characterized the stability of spin-cast PEDOT:PSS film on the 500 µm diameter conductor (Figure 4a, see the Experimental Section) in a similar experimental convention to electrodeposited PEDOT:PSS. Figure 4b–h demonstrates a surface morphology change of the same PEDOT:PSS/Au-nr electrode at different CV cycles (up to 11 000 cycles).…”
Section: Resultsmentioning
confidence: 99%
“…[5b] Recently, Boehler et al demonstrated sputtered iridium oxide film (SIROF) as an exceptional adhesion promoter layer for electrodeposited PEDOT coatings on macroscale electrodes (500 µm diameter), resulting in polymer survival for over 10 000 CV cycles and 110 days under accelerated aging conditions at 60 °C. [10] The efficacy of this approach for microscale PEDOT-coated electrodes and for spin-cast PEDOT – used recently in recording for the surface of human cortex [11] – is yet to be assessed for this technique.…”
Section: Introductionmentioning
confidence: 99%
“…One such project is Open Ephys, who have developed inexpensive hardware and freely available source code for electrophysiological data acquisition and analysis (webpage: http://www.openephys.org or wiki: https://open-ephys.atlassian.net/wiki/spaces/OEW/overview) (Siegle et al , 2017). This hardware/software combination has been widely adopted for animal neurophysiology studies and recently protocols for its use for EEG recordings in humans have been published (Black et al , 2017, Hermiz et al , 2016. To our knowledge this system has not been used for human microneurography where it may offer advantages.…”
Section: Introductionmentioning
confidence: 99%